2011
DOI: 10.1007/s12026-011-8242-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of regulatory T cells instigates functional down-regulation of cytotoxic T lymphocytes in human breast cancer

Abstract: Regulatory T (Treg) cells are a subpopulation of T cells with the ability to control the responses of both CD4+ and CD8+ T cells. A case-control study was conducted in order to determine the functional attributes of Treg cells within the breast cancer milieu. Triple-color flow cytometry was utilized to study the phenotype expression of CD4+CD25+ Treg cells and CD8+ T cells in autologous tumor-infiltrating lymphocytes (TILs) and peripheral blood lymphocytes (PBLs) derived from 33 patients with stage I-III breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Granzyme B is found to be expressed in breast carcinomas (Hu et al, 2003) and thought to be either protective or work as an immune regulator. More recent reports suggested that granzyme B may contribute to suppression of anti-T cell responses (Lindner et al, 2013) and may be highly expressed in Tregs in the tumor microenvironment (Li et al, 2011). Further mechanistic work to assess the relative levels of each T cell subset in the breast and distant metastatic sites isolated from non-stressed and stressed, and socially isolated mice is ongoing in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Granzyme B is found to be expressed in breast carcinomas (Hu et al, 2003) and thought to be either protective or work as an immune regulator. More recent reports suggested that granzyme B may contribute to suppression of anti-T cell responses (Lindner et al, 2013) and may be highly expressed in Tregs in the tumor microenvironment (Li et al, 2011). Further mechanistic work to assess the relative levels of each T cell subset in the breast and distant metastatic sites isolated from non-stressed and stressed, and socially isolated mice is ongoing in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Treg cells are likely to be involved in the escape of cancer cells from antitumor effector T cells [7]. Increased numbers of Treg cells have been in patients with different types of cancers [8][9][10][11][12]. These observations raise the possibility that a compensatory response to the increased density of Treg cells can be triggered in the body.…”
mentioning
confidence: 99%
“…Indicating that the transduction signal pathway of activation of IL-2 is the main pathway altered by OP compounds in lymphocytes [6]. Besides T CD4 lymphocytes, T CD8 cells have an essential role in some cellular processes, such as the cytotoxic response known as CTL to kill virus and cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Besides T CD4 lymphocytes, T CD8 cells have an essential role in some cellular processes, such as the cytotoxic response known as CTL to kill virus and cancer cells. Therefore, this subset of CD3 lymphocytes are very important as part of the immune response inducing clonal expansion of effectors and memory clones, which are determinant to control pathogens or cancer development [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation